No Effect of Return to Sport Test Batteries with and without Psychological PROs on the Risk of a Second ACL Injury: A Critical Assessment of Four Different Test Batteries - Ramana Piussi; Rebecca Simonson; Johan Högberg; Roland Thomeé; Kristian Samuelsson; Eric Hamrin Senorski (North American Sports Medicine Institute, 2023)
# Background Patients report psychological barriers as important when returning to sport, however, psychological outcome measures are seldom included in return to sport (RTS) assessment. There is a need for clinical trials to integrate psychological patient-reported outcomes (PROs) in return to sport batteries assessing patients treated with ACL reconstruction. # Objective The aim of this study was to determine the association between passing clinical tests of muscle function and psychological PROs and sustaining a second ACL injury in patients who RTS after primary ACL reconstruction. # Design Retrospective Cohort study # Methods Patients' sex, age, height and weight, and the results of strength and hop tests, as well as answers to PRO's (including Tegner activity scale, the ACL Return to Sport after Injury scale (ACL-RSI) as well as the Quality of Life (QoL) subscale of the Knee injury and Osteoarthritis Outcome Score \[KOOS\]), were extracted from a rehabilitation-specific registry. Four different test batteries comprising muscle function tests and PROs were created to assess whether patients were ready to RTS. Passing each of the test batteries (yes/no) was used as an independent variable. A multivariable Cox proportional hazard model analysis was performed, with sustaining a second ACL injury (either ipsi- or contralateral; yes/no) within two years of RTS as the dependent variable. # Results A total of 419 patients (male, n=214; 51%) were included, of which 51 (12.2%) suffered a second ACL injury within the first two years after RTS. There were no differences in passing rates in the different RTS test batteries comprising muscle function tests and PROs for patients who suffered a second ACL injury compared to patients who did not. # Conclusion No association between passing the RTS clinical tests batteries comprising muscle function and psychological PROs used, and the risk of a second ACL injury could be found. # Level of Evidence 3